(untitled) (Research, Society and Development, 2020)
The study evaluated the perception of the students enrolled in the technical course on oral health, in the city of Patos, Paraíba, about oral health for children from 0 to 36 months old. The research it was used the observational type, with an inductive approach and statistics-comparative and descriptive procedure, adopting as strategy of data collection a specific questionnaire. The sample covered 3 technical training centers in the city of Patos and it was composed of 81 participants. The results were analyzed descriptively and using the Fisher Exact statistical test, with significant level of 5%. Among the survey participants, 90.2% were female and 9.8% male. When evaluated on dental caries as a disease, most students (86.6%) said positively. Regarding the removal of biofilm in children from 0 to 36 months, 52.4% reported that the use of clean gauze constitutes the best form. However, when asked about the consumption of sweets in this age group, 70.7% said that it should be totally restricted and 50% answered that fluoride serves to avoid caries and get the tooth white. There is no statistically significant difference between the genus and the question "Can the milk tooth be restored?" (p=0.149), nor between the genus and the assertion "Which dentition is more important?" (p=0.310). It is concluded that there is a lack of knowledge about oral health in early childhood, since the students present specific small knowledge about the topic.